The potential of HBV cure: an overview of CRISPR-mediated HBV gene disruption - Yao, Zhi Q.; Schank, Madison B.; Zhao, Juan; El Gazzar, Mohamed; Wang, Ling; Zhang, Yi; Hill, Addison C.; Banik, Puja; Pyburn, Jaeden S.; Moorman, Jonathan P. (Frontiers in Genome Editing, 2024)
Hepatitis B virus (HBV) infection is a common cause of liver disease worldwide. The current antiviral treatment using nucleotide analogues (NAs) can only suppress de novo HBV replication but cannot eliminate chronic HBV infection due to the persistence of covalently closed circular (ccc) DNA that sustains viral replication. The CRISPR/Cas9 system is a novel genome-editing tool that enables precise gene disruption and inactivation. With high efficiency and simplicity, the CRISPR/Cas9 system has been utilized in multiple studies to disrupt the HBV genome specifically, eliciting varying anti-HBV effects both in vitro and in vivo. Additionally, multi-locus gene targeting has shown enhanced antiviral activity, paving the way for combination therapy to disrupt and inactivate HBV cccDNA as well as integrated HBV DNA. Despite its promising antiviral effects, this technology faces several challenges that need to be overcome before its clinical application, i.e., off-target effects and in vivo drug delivery. As such, there is a need for improvement in CRISPR/Cas9 efficiency, specificity, versatility, and delivery. Here, we critically review the recent literature describing the tools employed in designing guide RNAs (gRNAs) targeting HBV genomes, the vehicles used for expressing and delivering CRISPR/Cas9 components, the models used for evaluating CRISPR-mediated HBV gene disruption, the methods used for assessing antiviral and off-target effects induced by CRISPR/Cas9-mediated HBV gene disruption, and the prospects of future directions and challenges in leveraging this HBV gene-editing approach, to advance the HBV treatment toward a clinical cure.